GAMBARAN PENGETAHUAN KELUARGA TENTANG PENYAKIT HIPERTENSI DI WILAYAH KERJA UPTD PUSKESMAS GANDING KABUPATEN SUMENEP - Mujib Hannan (Wiraraja Medika : Jurnal Kesehatan, 2011)
Hypertension represent the chronical disease is which need the observation and handing non stoped continual, because otherwise get the day dream precisely can generate the complication of heart, brain, eye and kidney. All important matter incourse of healing of hypertension patient is family, because family can give the motivation for the life of healthy, desspitefully also family own the duty to recognize the troble of health growth of each, every its family member, taking decision to conduct action correct, giving treatment to ill family member and which cannot assit the their self of because handicap or its age is which under age or old, and also give the knowledge which enough to it’s family.Method: this research reresent the descriptive research with the approach of house hold survey, this sampel research amount to 44 people technicsly is samp[ling used is cosecutive sampling. Technics of date collecting with the documentation, interview, observation and questionnarre.Result  of research got by that pandemic family knowledge of hypertension is less with the biggest proportion that is resporder have age > 40 year (61,4%) education of respondent SD (56%) and respondent work as famer (50%).Conculussion: research is that pandemic family knowledge of hypertension less. In order that improving knowledge that is by providing medium-medium supporting like counselling program of about health, and also supported with the health energy with the going concern education system.